Divergence in Life History Traits between Two Populations of a Seed-Dimorphic Halophyte in Response to Soil Salinity - Yang, Fan; Baskin, Jerry M.; Baskin, Carol C.; Yang, Xuejun; Cao, Dechang; Huang, Zhenying (Frontiers in Plant Science, 2017)
Production of heteromorphic seeds is common in halophytes growing in arid environments with strong spatial and temporal heterogeneity. However, evidence for geographic variation (reflecting local adaptation) is almost nonexistent. Our primary aims were to compare the life history traits of two desert populations of this halophytic summer annual Suaeda corniculata subsp. mongolica and to investigate the phenotypic response of its plant and heteromorphic seeds to different levels of salt stress. Dimorphic seeds (F1) of the halophyte S. corniculata collected from two distant populations (F0) that differ in soil salinity were grown in a common environment under different levels of salinity to minimize the carryover effects from the field environment and tested for variation in plant (F1) and seed (F2) traits. Compared to F1 plants grown in low soil salinity, those grown in high salinity (> 0.2 mol•L-1) were smaller and produced fewer seeds but had a higher reproductive allocation and a higher non-dormant brown seed: dormant black seed ratio. High salinity during plant growth decreased germination percentage of F2 black seeds but had no effect on F2 brown seeds. Between population differences in life history traits in the common environment corresponded with those in the natural populations. Phenotypic differences between the two populations were retained in F1 plants and in F2 seeds in the common environment, which suggests that the traits are genetically based. Our results indicate that soil salinity plays an ecologically important role in population regeneration of S. corniculata by influencing heteromorphic seed production in the natural habitat.